Is there scientific relevance to the plot of films and documentaries about eating disorders? - Alessandra Honorio Boroski; Rosane Pilot Pessa; Janaína Cristina Pasquini de Almeida; Jacqueline de Souza (Associação Brasileira de Enfermagem, 2024)
ABSTRACT Objectives: to analyze films and documentaries about eating disorders from the last twenty years, identifying the way they approach the topic as well as their relevance for didactic use in teaching the health field. Methods: a descriptive study, whose data collection was carried out on the main streaming and video platforms, resulting in the survey of 60 media. Of these, only 25 had audio/subtitles in Portuguese (inclusion criteria). scientific relevance was analyzed considering psychopathological and epidemiological aspects of these disorders. A questionnaire about the plot, characters and descriptive data analysis were used. Results: most media were dramas about female teenagers who tried to conform to beauty stereotypes, whose symptoms portrayed converged with current medical diagnostic manuals. Conclusions: in practical terms, a classificatory list of 11 media was prepared that could be used as a teaching resource for teaching this topic in the health field.